2020
DOI: 10.1002/jclp.23066
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect interference and fear of happiness are independently associated with depressive symptoms

Abstract: Objectives Reward devaluation theory (RDT) posits that some depressed individuals avoid positivity due to its previous association with negative outcomes. Behavioral indicators of avoidance of reward support RDT, but self‐report indicators have yet to be examined discriminantly. Two candidate self‐report measures were examined in relation to depression: negative affect interference (NAI), or the experience of negative affect in response to positivity, and fear of happiness, a fear of prospective happiness. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…Our constellation of findings supports prior research that has found positive relationships between fear of happiness and depressive symptoms (Blasco-Belled et al, 2021;Gilbert et al, 2012;Jordan et al, 2021;Joshanloo et al, 2014;Lyvers et al, 2022;Şar et al, 2019) and provides evidence that the processing of positivity changes at different levels of depressive symptom severity when examined with a moderated network analysis. Notable moderating effects were present suggesting dampening and/or complete reversal (i.e., devaluation) of connections among positivity statements as depressive symptoms increased, providing evidence for a change in schemas and processing of positivity associated with change in depression symptom severity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our constellation of findings supports prior research that has found positive relationships between fear of happiness and depressive symptoms (Blasco-Belled et al, 2021;Gilbert et al, 2012;Jordan et al, 2021;Joshanloo et al, 2014;Lyvers et al, 2022;Şar et al, 2019) and provides evidence that the processing of positivity changes at different levels of depressive symptom severity when examined with a moderated network analysis. Notable moderating effects were present suggesting dampening and/or complete reversal (i.e., devaluation) of connections among positivity statements as depressive symptoms increased, providing evidence for a change in schemas and processing of positivity associated with change in depression symptom severity.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we examined the interactive relationships between the FHS variables via network analysis at varying levels of depressive symptom severity. Given that existing literature has shown (a) a high correlation of FHS to depressive symptoms (Blasco-Belled et al, 2021;Gilbert et al, 2012;Jordan et al, 2021;Lyvers et al, 2022), (b) depressed individuals have negative biases toward positivity and happiness (Winer & Salem, 2016), and (c) the negativity networks of depressed individuals are more densely connected than non-depressed individuals (Hayes et al, 2015), we expected differences in the network structures of FHS variables at different levels of depression, in line with the predictions for self-relevant processing of positivity and negativity by RDT. We investigated this using a MNM with the sum score of the Quick Inventory of Depressive Symptomatology Self-Report (QIDS-SR; Rush et al, 2003) as the moderator to examine how positivity interacts with negativity networks representing increasingly depressed individuals.…”
Section: Network Analysismentioning
confidence: 58%
See 1 more Smart Citation
“…Previous research reported that psychological maltreatment had a positive association with aversion to happiness (Lazić & Petrović, 2020;Sar et al, 2019), and young adults with insecure attachments also reported greater aversion to happiness (Joshanloo, 2018). Additionally, aversion to happiness was linked to depressive symptoms (Jordan et al, 2020), resilience (Yildirim, 2019), the externality of happiness , dispositional hope (Belen et al, 2020), subjective happiness (Joshanloo & Weijers, 2014), and subjective, emotional, and psychological wellbeing (Joshanloo, 2013(Joshanloo, , 2018Yildirim, 2019;Yildirim & Belen, 2018). Aversion to happiness was for example reported as a mediator in the relationship between attachment styles and subjective well-being among young adults (Joshanloo, 2018).…”
Section: Aversion To Happinessmentioning
confidence: 92%
“…Related to the second stage (i.e., attention allocation), studies using the dot-probe task as a measure of attention allocation, have revealed an attentional bias against positively valenced stimuli in depressed individuals. This bias manifests itself in discriminantly avoiding positive information compared to neutral information (Jordan et al, 2020). Attempting to modify this attentional bias, Vrijsen et al (2018) offered depressed inpatients a positivity attention or approach training aimed at inducing preferential processing of generally positive pictures over neutral ones.…”
mentioning
confidence: 99%